-(x+8)=-9x+56

Simple and best practice solution for -(x+8)=-9x+56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+8)=-9x+56 equation:


Simplifying
-1(x + 8) = -9x + 56

Reorder the terms:
-1(8 + x) = -9x + 56
(8 * -1 + x * -1) = -9x + 56
(-8 + -1x) = -9x + 56

Reorder the terms:
-8 + -1x = 56 + -9x

Solving
-8 + -1x = 56 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-8 + -1x + 9x = 56 + -9x + 9x

Combine like terms: -1x + 9x = 8x
-8 + 8x = 56 + -9x + 9x

Combine like terms: -9x + 9x = 0
-8 + 8x = 56 + 0
-8 + 8x = 56

Add '8' to each side of the equation.
-8 + 8 + 8x = 56 + 8

Combine like terms: -8 + 8 = 0
0 + 8x = 56 + 8
8x = 56 + 8

Combine like terms: 56 + 8 = 64
8x = 64

Divide each side by '8'.
x = 8

Simplifying
x = 8

See similar equations:

| (2c+5)(c+4)=0 | | 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= | | log(y)=1.9747log(x) | | 69x+9y=900 | | y=x^2+49 | | 6z-12z=1-18 | | 11n+9=6n+44 | | (9*4)-5=9*(4-5) | | -6h+4=-10h+16 | | 10p(4/5p) | | 5x+10-3x-3= | | y=4x^2+12x-5 | | -8x-18=-146 | | 4t-2=6t+6 | | -16x^2+80x= | | -5x*2x= | | x=1.8*x+32 | | 2x+14=-6x+34 | | a(n)=12+(n-1)(3) | | -6h+4=-10h+6 | | log(6x+12)=1+log(x-6) | | -2-y=-8(2+y) | | X*4+200=x*14-20 | | 50-10(x-5)= | | 6=30-8x | | 4(6v-1)(v-4)=0 | | F(x)=4x^2+32x | | 2x=55 | | 6u=3u+45 | | y*(2)*(-3)=30 |

Equations solver categories